Effects of pentagamavunon-0 (PGV-0) as alternative analgesics on orthodontic tooth movement in rats - Farmasyanti, Cendrawasih Andusyana; Kuijpers-Jagtman, Anne Marie; Susilowati, Heni; Meiyanto, Edy (Padjadjaran Journal of Dentistry, 2019)
Introduction: Some analgesic drugs may have adverse effects on bone remodelling and, thus, on orthodontic tooth movement rate (OTM). GV-0 is synthesized by reacting vanillin and cyclopentanone catalyzed in acidic condition, and it has been revealed as a selective COX-2 inhibitor. This study was aimed to investigate the effect of pentagamavunon-0 (PGV-0), one of the curcumin analogues, on OTM. Methods: This study was conducted on 50 male Wistar rats (350-450 g) which were randomly divided into five groups (n = 10 each): 1) no treatment group (NT), 2) orthodontic treatment only (ORT), 3) ORT plus 0.4% sodium carboxymethyl cellulose (Na-CMC) analgesic carrier, 4) ORT plus 200 mg/kg BW Paracetamol (PCT) as the positive control, and 5) ORT plus PGV-0 (50 mg/kg BW (PGV-0). Results: Drug and day interaction was statistically significant on two-way ANOVA. Post-hoc analyses showed that OTM increased from day 3 to 7 in all orthodontic groups over the same distance (p>0.05). Maximum OTM was found on day 6, which was significantly farther than the distance on day 4. On day 7, OTM was less than on day 6. OTM in all orthodontic groups, including in the PGV-0 group, was higher than in the NT group (p<0.05). No differences was seen in OTM between PGV-0 group and other orthodontic groups (p>0.05). Post-hoc analysis (intra days) revealed that OTM in PGV-0 and other orthodontic treatment groups increased. Conclusion: After a single orthodontic force, PGV-0 does not inhibit tooth movement in rats from day 1 to day 7. Therefore, it is possible to develop PGV-0 as an alternative analgesics during orthodontic therapy.Keywords: Analgesic drug, orthodontics, tooth movement, curcumin.